Influence and total antioxidant capacity of non-enzymatic antioxidants on the quality and integrity of extended and cryopreserved semen of Murrah buffalo (Bubalus bubalis) - Turaja, Kimberly I B.; Vega, Renato SA; Saludes, Thelma A.; Tandang, Abraham G.; Bautista, Jose Arceo N.; Salces, Agapita J.; Rebancos, Carmelita M. (2019)
The study compared the effect of non-enzymatic antioxidants on the % motility, livability, and plasma membrane integrity of the cryopreserved sperm from four purebred Murrah bulls aged 10?17 years old. The level of antioxidants was also determined. Experiment 1 was analyzed using 4 x 4 factorial design in a randomized complete block design (RCBD) with bulls blocked in four; in Experiment 2, it analyzed the levels of MegaAntiox using PROC ANOVA of SAS software. Results revealed no significant (P > 0.05) difference in post-thaw sperm motility (%) between antioxidants but a significant decrease (P < 0.05) in the post-thaw sperm motility was observed at Week 3. The addition of non-enzymatic antioxidants did not affect (P > 0.05) the live sperm though difference was observed on the livability of sperm cells in different collection weeks. In extended semen, the addition of non-enzymatic antioxidants did not show any significant effect (P > 0.05) on post-thaw sperm motility (%) and livability. After six months of cryopreservation, the addition of vitamin E (one of the non-enzymatic antioxidants) had a negative effect on the post-thaw sperm motility. Livability and PMI were not significantly affected (P > 0.05) by the different treatments. In conclusion, the addition of 0.1 mg/ml non-enzymatic antioxidants did not improve sperm motility (%) and the livability of the sperm. (Author's abstract)